overview of interrelationship between climate change and forests - Khaine, Inkyin; Woo, Su Young (Forest science and technology, 2015)
Global warming is a well-known natural phenomenon that needs to be controlled for environmental conservation. Based on the ecological interrelationship between forest and climate, the concept of our review was formulated with the aim of providing current information about deforestation and its effects on climate change, the impacts of climate change on forests and the role of forests in climate change. Based on recent research findings, the annual rate of deforestation is 0.14% per year with 2.3 million square kilometers lost between 2000 and 2012. The net carbon emission from deforestation and forest degradation, which can cause climate change, was high and it has not changed significantly over the last two decades. On the other hand, temperature, drought, precipitation and fire can affect forest health (especially for young trees). But if we define these factors in detail, solar radiation alone may not affect tree growth, although together with temperature it can affect growth. Moreover, the frequency of fire affected the regeneration of tropical moist deciduous and Amazonian forest types more significantly than temperate and tropical dry deciduous forest types. Non-equilibrium species distribution has been occurring and frequency of species has been changed throughout the world. However, the amount of carbon storage by world forests is significant (650 billion tons) although carbon sequestration potential varies with forest types and water deficiency.